PENGEMBANGAN JOGGING TRACK BERBASIS SUBAK: INOVASI EKOWISATA UNTUK PEMBERDAYAAN KEWIRAUSAHAAN DESA - Putu Diah Asrida; I Gede Agus Adi Saputra (Fakultas Teknik dan Informatika Universitas PGRI Mahadewa Indonesia, 2025)
This community service program aims to develop a local culture-based ecotourism model through the development of a jogging track integrated with the traditional Subak irrigation system. The activity was carried out in Bongkasa-Badung village, with a participatory approach and needs-based training methods. This program is not only directed at planning physical infrastructure development, but also at strengthening entrepreneurial capacity in a sustainable manner. There are seven strategic steps implemented, starting from initial observation, social mapping, to community training and coaching. The results of the community service show that the Subak jogging track can be an alternative ecotourism that is educational, environmentally friendly, and oriented towards preserving culture. Economically, various new business activities have emerged such as healthy stalls, farmers selling local products, and community-based local product management (tuak drinks). The main challenges in implementation are limited infrastructure and coordination between institutions. However, through the right communication strategy and contextual training, these obstacles can be overcome gradually. This community service provides practical implications for the development of locality-based tourism villages and is worthy of being replicated in areas with similar characteristics.